Characteristics of Airborne Suspended Dust in Hanoi City Using the SEM and PIXE Methods - Anh Le, Hoang; Duy Linh, Bui; Thanh Tuan, Nguyen; Quang Thang, Phan; Viet Thanh, Nguyen; Thu Huyen, Pham (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 2SDO - 10.25073/2588-1094/vnuees.5425, 2025)
Air pollution has become a pressing global concern due to its multifaceted impacts on the economy, society, and the environment. This study provides an in-depth investigation into the physicochemical pollution levels of Total Suspended Particulate (TSP) in inner-city and suburban areas of Hanoi, during both the dry and rainy seasons. TSP samples were collected using a high-volume air sampler. The morphology and particle size distribution of the TSP samples were analyzed using Field Emission Scanning Electron Microscopy, Scanning Electron Microscopy (SEM) combined with ImageJ software. The TSP samples were subsequently analyzed for major elements using the Particle Induced X-ray Emission (PIXE) method with a dedicated setup on a Pelletron 5SDH-2 accelerator system. The results show that TSP concentrations in the urban area (79.7 - 165.5 mg/m 3 ) were higher than in the suburban area (52.2 - 162.2 mg/m 3 ), and their concentrations in the dry season (60.8 - 165.5 μg/m³) were higher and exhibited greater fluctuation than in the rainy season (52.0 - 124.8 μg/m³). Coarse particles (PM 10 ) constituted the majority (>85%) of the TSP. The concentrations of 17 major elements detected in the TSP samples via PIXE were arranged in the following order: Si > Ca > S > Al > Na > K > Cl > Fe > Mg > Zn > P > Ti > Mn > Pb > Cr > Cu > Ni.